Multiple myeloma. - White TB; Caldwell D; Hall-Rollins J (Radiologic Technology)
OBJECTIVES: After completing this article, readers should be able to: Recognize the signs and symptoms of multiple myeloma. Discuss the process used to confirm a multiple myeloma diagnosis. Identify imaging modalities used to diagnose the disease. Describe the appearance of multiple myeloma on radiographic images. Explain the use of computed tomography, magnetic resonance and positron emission tomography in imaging of multiple myeloma. List traditional and newer multiple myeloma treatment options.